Integrated Plant Protection in Organic Agriculture - Tatia Khositashvili (Research Retrieval and Academic Letters, 2025)
Plant protection in organic farming involves not only replacing chemical agents with biological agents, but also they have a different attitude towards fighting. In organic farming, the main thing is not to fight plant diseases or pests, but to take measures that will prevent the spread of pests and diseases. Fungi, bacteria, viruses, mites, insects, which play the role of sanitary police in the plant world. But when these organisms multiply excessively and reduce the yield of cultivated plants, They belittle us, they appear to us as pests.